Economical and Environmentally Friendly Track of Biowaste Recycling of Scallop Shells to Calcium Lactate - Somkiat Seesanong; Yok Wongchompoo; Banjong Boonchom; Chuchai Sronsri; Nongnuch Laohavisuti; Kittichai Chaiseeda; Wimonmat Boonmee (My University, 2022)
The scallop shell waste (Pectinidae, one of saltwater clams) was used as a raw material (precursor) to prepare calcium lactate (Ca(C2H4OHCOO)2), and the physicochemical properties of scallop-derived calcium lactate were then investigated. The scallop waste was first ground to obtain calcium carbonate (CaCO3) powder, and the calcium lactate compounds were successfully synthesized by the reactions between shell-derived CaCO3 and lactic acid (C2H4OHCOOH). The short preparation time, high percentage yield, and low-cost production are the preferred manners, and, in this research, it was the reaction of 70 wt % lactic acid and scallop-derived CaCO3. The thermal decompositions of both CaCO3 precursor and all prepared calcium lactates resulted in the formation of calcium oxide (CaO), which is widely used as a catalyst for biodiesel production. By comparing with the literature, the results obtained from the characterization instruments (infrared spectrophotometer, X-ray diffractometer, thermogravimetric analyzer, and scanning electron microscope) confirmed the formation and crystal structure of both CaCO3 and its calcium lactate product. The morphologies of calcium lactate show different sizes depending on the acid concentration used in the reaction process. Consequently, this work reports an easy, uncomplicated, low-cost technique to change the cheap calcium compound product (scallop CaCO3) derived from shellfish waste to the valuable compound (calcium lactate), which can be used in many industries.
Keywords: Diffractometer; Biodiesel Production and Applications